2002
DOI: 10.21000/jasmr02010459
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Model to Predict Rainfall Use Efficiency of Pastures on Open-Cut Coal Mines in Central Queensland, Australia

Abstract: Abstract. Cattle grazing is a potential post-mining land-use option for open-cut coal mines in the dry sub-tropical region of central Queensland, Australia, but no research has been conducted to determine the grazing capacity of these lands. A study was conducted to develop a model for estimating pasture productivity of rehabilitated mined lands, from which long-term sustainable stocking rates could be predicted. Rainfall-use efficiency (RUE), a reliable indicator of pasture productivity in this moisture-limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Post-mining land has been returned to pastoral land use following rehabilitation with buffel grass in central Queensland (Bisrat et al 2004). …”
Section: Value For Other Purposesmentioning
confidence: 99%
“…Post-mining land has been returned to pastoral land use following rehabilitation with buffel grass in central Queensland (Bisrat et al 2004). …”
Section: Value For Other Purposesmentioning
confidence: 99%
“…Livestock grazing of pastures on rehabilitated land is a potential postmine land use (Mentis 1999;Ditsch et al 2006); however, there are few published examples of the viability of such rehabilitation in Australia. Bisrat et al (2004) and Grigg et al (2002) found that the calculated safe stocking rate for sown buffel grass pastures and cattle liveweight gain observed over 18 months on rehabilitated mining land at two sites in central Queensland was comparable to that on unmined land in the region. At a third mine, the safe stocking rates were lower due to steep slopes and sodic soils.…”
Section: Introductionmentioning
confidence: 98%
“…A shift in the area from pulses to cereals and from cereals to pulses was observed in Rabi and Kharif seasons, respectively. Bisrat [10] in his study on economic analysis of watershed treatment through groundwater recharge of Basavapura micro-watershed in Kolar district of Karnataka revealed that average yield of bore well increased from 1150 gallons per hour (GPH) to 1426 GPH that is by 24 per cent due to construction of water harvesting structures. Naidu (2001) in his study on Vanjuvankal watershed of Andhra Pradesh noticed that, because of water harvesting structures and percolation ponds the ground water level in watershed area showed a rise by 2 to 3 meters.…”
Section: Introductionmentioning
confidence: 99%